Perancangan Ulang Poros, Pasak, Kopling, dan Bearing Pompa Sentrifugal 5,5 kW/1450 RPM Berbasis Keandalan dan Validasi - Meilani, Rezki; Handoko, Susilo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This paper addresses a common gap in pump transmission design that relies on “allowable stress + safety factor.” This paper redesign a complete shaft key coupling bearing train of a 5.5 kW/1450 rpm centrifugal pump using a reliability based framework. A field case uses nameplate data and dimensional measurements. Methods include ASME/DE von Mises formulation for combined bending torsion, stress concentration factors for keyseat/fillet, consistent torque path sizing of key and flange coupling, and bearing L10 life per ISO 281. All calculations use SI units with ±5–10% uncertainty propagation. Results show an S40C shaft ds≈33.3 mm, a 10×8×15 mm key, a flange coupling passing shear/crushing checks, and an angular contact bearing meeting a 20–40 kh life target, sensitivity highlights Kt and equivalent bearing load as dominant drivers. This paper recommend as a design for reliability guide for maintenance friendly pump trains in SME/utility settings, complemented by targeted vibration tests.